Total Flavonoids of Chuju Decrease Oxidative Stress and Cell Apoptosis in Ischemic Stroke Rats: Network and Experimental Analyses - Wang, Cong; Chen, Hao; Jiang, Hui-hui; Mao, Bin-bin; Yu, Hao (Frontiers in Neuroscience, 2021)
Abstract Background: Pharmacological research results showed that flavonoids of Chuju (TFCJ) could be used to treat acute myocardial ischemia and myocardial ischemia-reperfusion injury. In this study, we explored the protective effect of TFCJ on ischemic stroke (IS) in the IS rat model. We hypothesized that TFCJ might exert its neuroprotective effects by suppressing apoptosis and oxidative stress that are closely related to PI3K/Akt/mTOR signaling pathway. Method: TFCJ (10, 20, 40 mg/kg) was administered for 7 days. Rats (260 ± 20 g) were subjected to middle cerebral artery occlusion (MCAO) for 2 h and reperfusion for 24 h. The neuroprotective effect of TFCJ was substantiated in terms of neurological deficits, oxidative stress (superoxide dismutase, glutathione peroxidase, catalase, and malondialdehyde), pathomorphological changes (HE staining and TUNEL staining), and neurobehavioral functions in the rats. Then, we employed network pharmacology to reveal the potential mechanism of TFCJ against IS. Western blot was used to determine the levels of PI3K/AKT/mTOR pathway proteins. The expression of BCL-2, BAX, and cleaved-Caspase-3 was also measured by Western blots and RT-PCR. Results: The histopathological assessment showed that TFCJ reduced MCAO-induced brain damage. Besides, TFCJ exerted a protective role in MCAO rats by alleviating cell apoptosis and oxidative stress. Network pharmacology showed that TFCJ might be used against IS through the PI3K/AKT signaling pathway. TFCJ reduced cell apoptosis and oxidative stress by increasing the level of p-AKT and p-mTOR in MCAO rats, while the effect of TFCJ was significantly reversed when applying LY294002 (PI3k inhibitor). Conclusion: These results indicated that TFCJ might decrease oxidative stress and apoptosis that are closely related to PI3K/Akt/mTOR pathway in IS. TFCJ is a promising authentic traditional Chinese medicine for the management of IS.